PERSONAL ATTITUDE AND MODALITY IN NARRATIVE FICTION - Narzullayeva Mohina (Ustozlar uchun, 2025)
This article explores how personal attitudes are expressed through modality in narrative fiction. Drawing on pragmatic and stylistic theories, the study investigates how authors use modal verbs, adverbs, and subjective language to convey evaluation, doubt, certainty, and emotion. The analysis focuses on selected excerpts from 20th-century English prose, highlighting how modality contributes to character development and narrative stance. The findings suggest that modality serves as a central tool in the construction of subjectivity and narrative voice.